Scaling Properties of ∅-Meson and Light Charged Hadron Production in Small and Large Systems at PHENIX - Nouicer Rachid (EPJ Web of Conferences)
Recent results on the identified charged-hadron (π±, K±, p, p¯) production vat midrapidity region (|η| < 0.35) have been measured by the PHENIX experiment in p + Al, 3He + Au, Cu + Au collisions at √SNN = 200 GeV and U + U collisions at √SNN = 193 GeV. These measurements are presented through the invariant transverse-momentum (pT ) and transverse-mass (mT) spectra for different collision centralities. The averaged freeze-out temperature value for different systems was found to be 166.1 ± 2.2 MeV, and do not exhibit any dependence on the collision centrality and 〈Nparti〉 values. The particle ratios of K/π and p/π have been measured in different centrality ranges of large and small collision systems. The values of K/π ratios measured in all considered collision systems were found to be consistent with those measured in p+p collisions. Furthermore, the identified charged-hadron nuclear-modification factors (RAB) are also presented. Enhancement of proton RAB values over meson RAB values was observed in central 3He+Au, Cu+Au, and U+U collisions. The proton RAB values measured in p+Al collision system were found to be consistent with RAB values of ∅, π±, K±, and π0 mesons, suggesting that the size of the system produced in p+Al collisions is too small for recombination to cause a noticeable increase in proton production.